개선된 인젝터를 이용한 저산화 버너(underoxidized burner utilizing improved injectors) (1997)
공기 또는 산소와 혼합되도록 디젤등의 액체 또는 기체 연료를 수용하여 스파크 플러그에 의해 점화시키기 위한 1단 또는 다단 내부 연소실(10)을 가진 저산화 버너에 이용되는 인젝터가 개시된다. 인젝터는 공기 및 연료를 배플(45)을 가진 혼합 장치로 동시에 공급하기 위한 급송 도관들(46,47)을 포함하며 분리되어 분사된 공기 및 연료가 상기 배플에 충돌되어 점화, 연소 및 배기되는 완전한 공기/연료 혼합물로 된다. 상기 인젝터는 연료로부터 최대 수소 H를 발생시키도록 물과 혼합하기 위해 배출 가스들을 수용한다. 연소실내에서 겹쳐지며 방향이 역전되는 층류가 형성된다. Injectors are disclosed for use in an underoxidized burner having a single or double stage internal combustion chamber (10) for receiving gaseous or liquid fuel such as diesel for mixture with air or oxygen and subsequent ignition by a spark plug. The injector includes feed conduits or tubes (46, 47) for simultaneously conducting air and fuel to a mixing device having a baffle (45) arrangement against which separately injected air and fuel impinge causing a complete air/fuel blending which is ignited, burned and exhausted. The injector may accept effluent gases for mixing with water to produce maximum hydrogen H2 from fuels. A laminar flow is produced which is folded over and reversed in direction within the combustion chamber.